2017
DOI: 10.21873/anticanres.11482
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Treatment of Earlystage Small-cell Lung Cancer

Abstract: Abstract. Background Small-cell lung cancer (SCLC) classified as early stage at the point of diagnosis is very rare representing only 5% of all SCLC patients (1). The low incidence of early stage SCLC is mainly attributable to highly aggressive biology, rapid tumour growth, the absence of early symptoms and a lack of established screening programs (2, 3).Radiochemotherapy remains the standard treatment in limited stage SCLC resulting in a median overall survival of 16-20 months (2-4). Several biomarkers such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“… 28 , 29 A small retrospective study indicated that PCI was a significant predictor of survival in patients with stage I to II SCLC treated with chemoradiotherapy. 30 However, it has not been established whether PCI is essential, especially for stage I patients. In our series, distant metastases were a major pattern of recurrence, and the brain was one of the frequent sites of distant metastases (as was the liver).…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 29 A small retrospective study indicated that PCI was a significant predictor of survival in patients with stage I to II SCLC treated with chemoradiotherapy. 30 However, it has not been established whether PCI is essential, especially for stage I patients. In our series, distant metastases were a major pattern of recurrence, and the brain was one of the frequent sites of distant metastases (as was the liver).…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications have already identi ed further prognostic factors associated with prolonged OS, like female sex 29303132 , KPS ≥ 70 33 respectively Eastern Cooperative Oncology Group (ECOG) performance status 0-1 3432 or N-Stage 0-2 33 as well as therapy-related factors like radiation dose > 52 Gy 33 or PCI. 35 In our analysis, trend of protective in uence of female sex, KPS 80-100 in OS were detected but insigni cant.…”
Section: Discussionmentioning
confidence: 50%
“…But it must be noted that due to the wide confidence interval in these results, a negative effect on OS and PFS cannot be ruled out. Previous publications have already identified further prognostic factors associated with prolonged OS, like female sex [ 30 33 ], KPS ≥ 70 [ 34 ] respectively Eastern Cooperative Oncology Group (ECOG) performance status 0–1 [ 33 , 35 ] or N-Stage 0–2 [ 34 ] as well as therapy-related factors like radiation dose > 52 Gy [ 34 ] or PCI [ 36 ]. In our analysis, a trend of protective influence of female sex, KPS 80–100 in OS were detected but insignificant.…”
Section: Discussionmentioning
confidence: 99%